Perbandingan Kinerja Keuangan antara Bank Umum Konvensional dan Bank Umum Syariah di Indonesia - Abdus Samad; Edy Anan (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2017)
The purpose of this research is to compare the financial performance between Commercial Conventional Bank and Commercial Sharia Bank in Indonesia on 2010-2015 periods using the financial ratios. The ratios that used in this research is LDR/FDR, CAR, ROA, BOPO, and NPL/NPF. Sample of this reasarch’s collected by using purposive sampling technique, the sample was chosen when it fulfilled the criteria that has been determined before.Financial ratios data in this research obtained from Published Financial Statement of Commercial Conventional Bank and Commercial Sharia Bank from 2010 to 2015 that published by each bank’s group. There were 144 samples obtained to be studied from Commercial Conventional Bank and 144 samples obtained to be studied from Commercial Sharia Bank in Indonesia.Method that used to analyze the data was independent t-test. The result of this research shown that there are significance difference between liquidity aspect, profitability aspect, solvability aspect, and asset’s quality aspect of Commercial Conventional Bank and Commercial Sharia Bank. Generally, the Financial Performance of Commercial Conventional Bank better than Commercial Sharia Bank.